The relationship between Motorcycle Rider Behaviour Questionnaire scores and crashes for riders in Australia. (May 2017) - Stephens, A.N.; Brown, J.; de Rome, L.; Baldock, M.R.J.; Fernandes, R.; Fitzharris, M.
Highlights: This study used the Motorcycle Rider Behaviour Questionnaire (MRBQ) with a representative sample of riders in Australia. Exploratory factor analysis showed a 29 item, five-factor solution best fit the data. MRBQ factor scores differed across riders who reported crashes compared with those who did not. Logistic regression showed that stunts were associated with increased crash risk. Speed violations and control errors scores were associated with near-crashes. Abstract: Motorcycle riders are over-represented in road fatalities in Australia. While riders represent 18% of the road users killed each year, motorcycle registrations constitute only 4.5% of the registered vehicle fleet. The Motorcycle Rider Behaviour Questionnaire (MRBQ) was developed with a view toward understanding behaviours likely to be associated with crash risk. These include behaviours that are either intentional (such as violations of road and speed regulations and stunts ) or unintentional (such as errors relating to traffic or control of the motorcycle), as well as protective behaviours related to use of safety equipment. The dual aims of the current study were, first, to determine the appropriate structure of a modified version of the MRBQ for use in a representative sample of riders in Australia and, second, to understand which MRBQ factors are associated with crash involvement. A stratified sampling procedure was undertaken to ensure the socio-economic status of local government area, age and gender of the sample was representative of the broader population of riders in New South Wales, Australia. The sample consisted of 470 riders (males = 89%). Exploratory factor analysis revealed a 29-item, five factor structure was suitable on the Australian data encompassing traffic errors, speed violations, protective gear, control errors and stunts . Overall, riders reported relatively safe behaviours, with frequent use of protective gear and infrequent aberrant behaviours. However, even though infrequent, violations of speed and errors related to control of the motorcycle increased the odds of near-crash involvement, whilst stunt behaviours were associated with increased odds of crash involvement. Interventions and countermeasures need to target these specific behaviours.